An Ontology for Context-aware Middleware for Dependable Medical Systems - Cerqueira, Jorsiele (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2022)
In healthcare systems, there is an ecosystem of heterogeneous biosensors. A middleware is required for transmitting and establishing dependable communication with multiple integrations and information exchange through messages. However, in environments in which a distributed and dynamic network exists, a purely traditional middleware would not minimize the effect failures at data transmission and network congestion can cause. To preserve data integrity and provide relevant services as the environment changes, the use of context-aware middleware is recommended. This article describes an ontology for context-aware middleware to handle challenges faced by medical system networks and environment changes.